Dimensi Kepentingan dalam Pengembangan Kelembagaan Ketahanan Pangan Lokal : Studi Kasus Program Aksi Mandiri Pangan di Desa Jambakan, Kecamatan Bayat, Kabupaten Klaten, Propinsi Jawa Tengah - Masithoh, Siti; Sumarti, Titik; Pranadji, Tri (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2009)
The issues of food security and poverty are basically two important points that have a strong relation to rural community development. A study was conducted to understand more on the depth of the relation between food security and local initiatives development. The aim of this research is to figure out how small peasant households build their institutions as they react to fulfill food security needs. The study is also to understand what type of intervention programs have been developed by the government and community, especially those concentrating in rural food-security. The study also seeks to find the answer of how deep had the peasants’ interest and initiatives been considered to be important part of food-security development program. Las but not least it was devoted to identify the current state of food-security situation of peasant’s household in rural areas. The research was carried out in Jambakan Village, Bayat Sub-district of Central Java Province. The method used in this study was community study (through survey and qualitative approaches and case study). The results of the study are: the implementation of food self reliant village program run by the government was not quite successful to accomplish due to governance problematic at local level. Some key factors explaining the relationship between the successfulness of the program and food security’s achievements are technical assistance, community organizers, trust, and leadership